2015
DOI: 10.1038/cddis.2015.257
|View full text |Cite
|
Sign up to set email alerts
|

Mahogunin regulates fusion between amphisomes/MVBs and lysosomes via ubiquitination of TSG101

Abstract: Aberrant metabolic forms of the prion protein (PrP), membrane-associated CtmPrP and cytosolic (cyPrP) interact with the cytosolic ubiquitin E3 ligase, Mahogunin Ring Finger-1 (MGRN1) and affect lysosomes. MGRN1 also interacts with and ubiquitinates TSG101, an ESCRT-I protein, involved in endocytosis. We report that MGRN1 modulates macroautophagy. In cultured cells, functional depletion of MGRN1 or overexpression of CtmPrP and cyPrP blocks autophagosome–lysosome fusion, alleviates the autophagic flux and its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…Maturation of late endosomes, generation of amphisomes and lysosomal proteolytic activity also does not get perturbed in these conditions (Majumder and Chakrabarti, 2015). Hence, we sought to confirm that the mitochondrial changes observed in MGRN1-depleted cells were due to GP78, and cells were co-transfected with different MGRN1 and GP78 constructs in the indicated combinations.…”
Section: Gp78 Is Downstream Of Mgrn1 During Mitochondrial Clustering mentioning
confidence: 98%
“…Maturation of late endosomes, generation of amphisomes and lysosomal proteolytic activity also does not get perturbed in these conditions (Majumder and Chakrabarti, 2015). Hence, we sought to confirm that the mitochondrial changes observed in MGRN1-depleted cells were due to GP78, and cells were co-transfected with different MGRN1 and GP78 constructs in the indicated combinations.…”
Section: Gp78 Is Downstream Of Mgrn1 During Mitochondrial Clustering mentioning
confidence: 98%
“…A recent study from our laboratory has shown that the ubiquitination of TSG101 is important in the fusion of lysosomes with autophagosomes and amphisomes; this maintains the intracellular autophagic flux and its degradative competence. Thus, loss of ubiquitinated TSG101 leads to build up of toxic cargo in cells because of impaired lysosomal fusion . Furthermore, loss of ubiquitinated functional TSG101 effectuates accumulation of unfolded proteins in the lumen of endoplasmic reticulum (ER), triggering ER stress; prolonged ER stress leads to apoptosis in cultured SHSY5Y (human neuroblastoma) and HeLa (human cervical cancer) cells .…”
Section: Escrt Proteins and Their Role In Neurogenesis And Neurodegenmentioning
confidence: 99%
“…Homozygous knockout animal for the ESCRT‐I protein, TSG101, is embryonically lethal . Depletion of TSG101 in cellular systems show enlarged lysosomes enriched with LC3 without perturbation of LAMP‐1 or CTSD trafficking and localization, suggesting its involvement in autophagic pathway . Furthermore, TSG101 dysfunction causes accumulation of autophagosomes due to inhibition of fusion of autophagosomes/amphisomes with lysosomes .…”
Section: Linking Escrt Pathway To Cell Death During Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations